CWANA Regional Agronomy Community of Practice (ACoP) to exchange knowledge and learnings to accelerate adoption of science based innovations - Devkota Wasti, Mina Kumari; Devkota, Krishna (International Center for Agricultural Research in the Dry Areas, 2023)
The CGIAR Initiative on Fragility to Resilience in Central and West Asia and North Africa (F2R CWANA) has been established for each of the targets countries Agronomy Communities of Practice (ACoP) in Egypt, Sudan and Uzbekistan to stimulate the delivery and adoption of science-based innovations at scale to increase food and nutritional security with resilience. The establishment of ACoP in these countries is crucial to the exchange and dissemination of knowledge and learnings and foster collaboration amongst scientists, which is hindering technology transfer and overall agricultural development. ACoP bridges experts and practitioners and leverages the diverse expertise within the community to foster sustainable agricultural development.